Single Channel Speech Enhancement Using Masking Based on Sinusoidal Modeling - Buragohain, Rantu; Reddy, R. Aditya; Venkatesh, Yenduri; Prabhakar, Gudmalwar Ashishkumar; Rao, Ch. V. Rama (Recent Trends in Image Processing and Pattern Recognition, 2022)
This paper focused on development of single channel speech enhancement method. Conventional noise reduction methods based on filtering like Wiener filtering and masking uses spectral magnitudes. These magnitudes are obtained from time-frequency representation of noisy speech signals. Here, speech signal is analyzed using sinusoidal modelling. Filter gain is developed for masking of the background noise based on sinusoidal components. The developed system’s performance is evaluated using Perceptual Evaluation of Speech Quality (PESQ). It is evident from experiments that proposed approach displaying better performance compared to existing approaches.